2016
DOI: 10.1038/srep26577
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Enhances Migration of Minature Pig Bone Marrow Mesenchymal Stem Cells Through Inhibition of RhoA-GTP Activity

Abstract: Bone marrow mesenchymal stem cells (BM-MSCs) are used in tissue engineering because of their migration characters. However, BM-MSCs have limitations in terms of reaching injuries and self-renewal. Therefore, enhancement of BM-MSC migration is important for therapeutic applications. Here, we assessed whether galectin-3 (Gal-3) increases the migration of minature pig BM-MSCs. Gal-3 was knocked down by short hairpin RNA (shRNA) or overexpressed using a lentiviral vector in Wuzhishan minature pig BM-MSCs. Prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Gal-3 was recently found to promote migration of MSC through inhibition of RhoA-GTP activity, enhancement of p-AKT (ser473) expression, and regulation of p-Erk1/2 levels [29]. Based on these data and in our findings, it is reasonable to suggest that Gal-3 plays a significant role in MSC migration and homing, which could have several implications in a cell transplantation setting.…”
Section: Discussionsupporting
confidence: 79%
“…Gal-3 was recently found to promote migration of MSC through inhibition of RhoA-GTP activity, enhancement of p-AKT (ser473) expression, and regulation of p-Erk1/2 levels [29]. Based on these data and in our findings, it is reasonable to suggest that Gal-3 plays a significant role in MSC migration and homing, which could have several implications in a cell transplantation setting.…”
Section: Discussionsupporting
confidence: 79%
“…A role for LGALS3 as a positive regulator of AKT is well established (36, 37), and LGALS3's regulation of AKT appears to be important for migration in pig MSC (38). We examined AKT expression and AKT phosphorylation in MSC transduced with control lentivirus and MSC transduced with LGALS3 shRNA and found phosphorylation of AKT at serine 473 was reduced by roughly half (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of LGALS3 in MSC reduces MSC abilit y to inhibit T cell function (24, 44). Recent studies have suggested LGALS3 plays an important role in MSC migration (38, 47). A study of LGALS3 in murine MSC revealed that the galectin is elevated in MSC as mice age (48).…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of Gal-1 could promote not only repair and regeneration but also tumor metastasis in the tumor microenvironment (84,85). Besides, Gal-3 has been reported to have similar functions (86)(87)(88). However, compared to Gal-1, Gal-3 is more similar to Gal-9 in immunosuppression properties.…”
Section: Gal-1 and Gal-3mentioning
confidence: 99%
“…Direct coculture system (87) Complete medium supplemented with 10% FBS (88) Complete medium (90) Complete medium supplemented with 11% FBS (77) PD-L1 sPD-L1 PD-1 CD80 RGMb…”
Section: Receptor Typementioning
confidence: 99%